Comparative outcomes of surgical fixation versus conservative management in clavicle fractures: A prospective cohort study. - Anup Kumar Padamwar; Dr. Keyur Jain (Student's Journal of Health Research Africa)
Background This study aimed to compare the clinical outcomes of conservative versus surgical intervention in patients with clavicle fractures.